Relevansi Pemikiran Pendidikan Ki Hajar Dewantara Pada Abad Ke-21 - Salihin Salihin; Liesna Andriany (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The 21st century has led to many transitions, mainly related to the instructional paradigm from teacher-centred to student-centred. This paradigm demands meaningful activities that emphasise learning and are able to build motivation to learn well. This has relevance to Ki Hadjar Dewantara's ideas regarding his concept of education which focuses on the question of how to become a complete human being. Therefore, this narrative literature study aims to provide a descriptive explanation of Ki Hadjar Dewantara's ideas related to the 21st century learning perspective based on existing literature. This article reveals that the ideas inherited by Ki Hadjar Dewantara have strong relevance to the construction of 21st century learning. The discussion of the relevance will be explained in this article as a common reflection for many people, especially educational agents